Research on the Construction of Coal Powder Settling Final Velocity Model for Coalbed Methane Wells in Panhe Block - Zhou Zhang; Wanying Yu; Min Zhou; Pengxiang Wang; Jintao Zhang; Yunxing Cao; Baoan Xian; Yibing Wang; Fei Zhang (Energy Science & Engineering)
ABSTRACT In response to the severe problem of coal powder production in the Panhe block coalbed methane wells in the southern Qinshui Basin, the characteristics of coal powder production in the study area were identified through sample testing, indoor experiments, and theoretical calculations. The settling velocity of coal powder with different mesh sizes was clarified, and a correction factor α was proposed for the experimental and theoretical results of settling velocity. The research results indicate that the coal powder concentration in the Panhe block ranges from 0.03 to 7.14 g/L, with an average of 1.26 g/L. The particle size of the coal powder produced was 4.10–237.64 μm, with an average of 35.82 μm. The settling velocity of coal powder particles with a mesh size of 40–400 is between 0.0041 and 0.029 m/s. The larger the particle size of coal powder particles, the higher the settling velocity of coal powder; the correction coefficient ranges from 2.3 to 13.67. A corrected settling velocity calculation model was obtained by fitting the coal powder particle size data to the correction coefficient. The research results provide a theoretical basis for developing production conditions, coal powder prevention, and control measures for coalbed methane wells in the Panhe area.